Evaluation of infants by echo planar imaging after repair of diaphragmatic hernia. Issue 2 (February 1988) - O'Callaghan, C; Chapman, B; Coxon, R; Howseman, A; Jaroszkiewicz, G; Stehling, M; Mansfield, P; Milner, A D; Swarbrick, A; Small, P
Abstract : Three infants were studied by echo planar imaging after repair of congenital diaphragmatic hernias. Total lung volume and individual lung volumes were estimated using echo planar imaging. In the two patients with left sided hernias, the right lung was more than twice as large as the left. The patient with a right sided hernia had developed emphysema on the right side, and the right lung was twice as large as the left when estimated by echo planar imaging. Echo planar imaging studies took less than five minutes to perform and no sedation was required.